Neonatal Maternal Separation Augments Carotid Body Response to Hypoxia in Adult Males but Not Female Rats - Soliz, Jorge; Tam, Rose; Kinkead, Richard (Frontiers in Physiology, 2016)
Perinatal exposure to adverse experiences disrupts brain development, including the brainstem network that regulates breathing. At adulthood, rats previously subjected to stress (in the form of neonatal maternal separation; NMS) display features reported in patients suffering from sleep disordered breathing, including an increased hypoxic ventilatory response and hypertension. This effect is also sex-specific (males only). Based on these observations, we hypothesised that NMS augments the carotid body’s O2-chemosensitivity. Using an isolated and perfused ex vivo carotid body preparation from adult rats we compared carotid sinus nerve (CSN) responses to hypoxia and hypercapnia in carotid bodies harvested from adult rats that either experienced control conditions (no experimental manipulation) or were subjected to NMS (3h/day from postnatal days 3 to 12). In males, the CSN response to hypoxia measured in preparations from NMS males was 1.5 fold higher than controls. In control rats, the female’s response was similar to that of males; however, the increase in CSN activity measured in NMS females was 3.0 times lower than controls. The CSN response to hypercapnia was not influenced by stress or sex. We conclude that NMS is sufficient to have persistent and sex-specific effects on the carotid body’s response to hypoxia. Because NMS also has sex-specific effects on the neuroendocrine response to stress, we propose that carotid body function is influenced by stress hormones. This, in turn, leads to a predisposition towards cardio-respiratory disorders.